A new crocodylomorph tooth assemblage from the Tataouine Basin and comments on the stratigraphic context of the Douiret Formation - Dridi, J. (Annales de paléontologie (1982), 2020)
A new crocodylomorph tooth assemblage from the Lower Member of the Douiret Formation (uppermost Jurassic–lowermost Cretaceous) in southeastern Tunisia is described. These teeth have been grouped into five morphotypes based on their diagnostic morphological features. The sample includes teeth, which have not been reported until now, such as non-Machimosaurini teleosauroid teeth, and labiolingually compressed tooth crowns with cutting edges devoid of serrations. Certain minor morphometric differences have been interpreted as ontogenetic or being possibly related to the position of the teeth in the jaws. Three trophic entities have subsequently been defined on the basis of the morphological characteristics of the teeth, and a possible niche partitioning between at least three crocodylomorph taxa is highlighted for the first time in the Tataouine Basin. On the other hand, the stratigraphic context of the Douiret Formation is thoroughly discussed in order to show how stratigraphic uncertainties could significantly impact previous attempts at reconstructing the macroevolutionary history of Crocodylomorpha. The latter should be treated with caution when the stratigraphic context of the fossil bearing formation remains a subject of debate. Un nouvel assemblage de dents de crocodylomorphes du membre inférieur de la Formation Douiret (Jurassique terminal-début du Crétacé inférieur) au Sud de la Tunisie est décrit. Les dents ont été groupées dans cinq différents morphotypes en se basant sur leurs caractéristiques morphologiques. Certaines dents n’ont pas été décrites jusqu’à présent, comme les dents de crocodylomorphes téléosauroïdés non Machimosaurini et celles comprimées labiolingualement et dotées de carènes tranchantes et non denticulées. Certaines différences morphométriques mineures semblent être liées au développement ontogénétique ou à la position des dents sur les rangées dentaires des mâchoires. Trois principales adaptations trophiques ont été définies grâce aux caractéristiques morphologiques dentaires, et au moins trois espèces de crocodylomorphes auraient évité la compétitivité alimentaire en partageant leurs ressources dans un écosystème remarquablement productif. D’autre part, le contexte stratigraphique de la Formation Douiret est discuté dans le but de montrer comment les incertitudes liées aux observations stratigraphiques pourraient impacter considérablement la reconstitution de l’histoire macroévolutive des Crocodylomorpha. Cette dernière doit être traitée avec précaution lorsque le contexte stratigraphique de la formation encaissante est un sujet débattu.